Distribution of blaCTX-M, blaSHV, blaTEM genes in Extended Spectrum β-Laktamase Producing Klebsiella pneumoniae from Clinical Isolates in Jakarta - Engel, Yulia; Conny Riana Tjampakasari; Fithriyah Sjatha (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2025)
Klebsiella pneumoniae is one of the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.) due to their high level of antibiotic resistance. Ceftriaxone is one of the cephalosporin antibiotic that functions inhibit bacterial cell wall synthesis and used for treating K. pneumoniae infections. Resistance to ceftriaxone in K. pneumoniae has been widely reported, with one contributing factor being the production of β-lactamase enzymes encoded by the genes blaCTX-M, blaSHV, and blaTEM. This study characterized the presence of these genes in 12 clinical isolates of K. pneumoniae and analyzed their correlation with phenotypic resistance to ceftriaxone. All isolates characterized with antimicrobial susceptibility testing (AST) and disk diffusion methods to evaluate the phenotypic production of blaCTX-M, blaSHV, and blaTEM. Molecular analysis using the polymerase chain reaction (PCR) method showed the genes blaCTX-M and blaTEM were detected in 11 isolates (91.67%), and blaSHV was found in 9 isolates (75%). The distribution pattern of the blaCTX-M, blaSHV and blaTEM resistance genes was present in 8 isolates (66.67%), with MIC values > 64 µg/mL. The presence of blaCTX-M, blaSHV, and blaTEM genes together in K. pneumoniae isolates represents a potential risk for resistance to other β lactam antibiotics.